"Can I Be at Risk of Getting AIDS?" A Linguistic Analysis of Two Internet Columns on Sexual Health - Harvey, Kevin; Locher, Miriam A.; Mullany, Louise (Linguistik Online, 2014)
Recent global statistics highlight that, out of all new cases of HIV infection, 45% are diagnosed in young people (UNAIDS 2008). Despite a range of new initiatives aimed at increasing young people's knowledge of HIV at the beginning of the first decade of the twenty-first century (UNAIDS 2001), latest figures highlight that such initiatives have not been wholly successful in preventing new infection in young people (UNAIDS 2011). In light of this, the language patterns that young people use when seeking information about HIV/AIDS are investigated. Our focus in particular is on computer-mediated-communication, a relatively under-researched area in the sphere of health communication. Building on previous research (Locher 2006, 2010; Harvey et al. 2008; Harvey 2013), we examine one UK and one US Internet-based, professional, health advice column as sources of advice-information for young people. Despite numerous established health campaigns, young advice-seekers' questions reflect misinformed conceptions, such as the conflation of HIV and AIDS and confusion as to the way in which the virus can be contracted. Our linguistic research gives access to young people's lay beliefs about sexual health and highlights the need to redress such beliefs, with the aim of improving the effectiveness of health education initiatives. We suggest that computer-mediated communication can be one effective medium through which to assess young people's knowledge about HIV/AIDS, as well as effectively disseminating sexual health advice and information by health care bodies.